"Women easily feel that they have lost a year if they don't ski faster": Finnish ski coaches' discursive constructions of gendered dual career pathways. (January 2023) - Saarinen, Milla; Ryba, Tatiana V.; Kavoura, Anna; Aunola, Kaisa
Abstract: Objectives: Earlier qualitative researchers studying athletes' dual careers (DCs) have shown that sociocultural discourses on gender are ingrained in DC policies and practices, creating gender inequalities and hierarchies. In this study, we aimed to extend this body of research by examining how Finnish elite youth ski coaches discursively construct athletes' education and gender in their talk and coaching practices. Similarly, we examined how coaches' beliefs about athletes' holistic development are interlinked with broader sociocultural discourses on gender. Design: Qualitative study. Methods: We conducted semi-structured interviews with 10 Finnish ski coaches (seven male, three female) aged 25–62 years (M = 38.5), and then analyzed the data using reflexive thematic analysis, interpreted through a feminist poststructuralist lens. Findings: Coaches' discursive practices regarding education depended on their athletes' ages. For athletes in secondary education, the coaches predominantly drew on DC discourses that emphasized the compatibility of sports and education, but for athletes transitioning to senior-level sports, they drew on dominant performance discourses, believing that athletes at the senior level should prioritize their sports. Moreover, coaches discursively constructed athletic development as especially important for female athletes, who were perceived as less capable of excelling in sports and therefore needing to invest in multiple careers. Conclusions: By drawing on gender stereotypes and binary understandings of gender, the coaches discursively reproduced gender hierarchies and unequal power relations in sports. These gendered discourses influence athletes' DC aspirations and the gendering of DC pathways. Highlights: This study is part of the Finnish Longitudinal Dual Career Study (Ryba et al., 2016). Sociocultural discourses of gender are ingrained in dual career policy and practice. Coaches' beliefs on athletes' holistic development are interlinked with discourses of gender. Coaches reproduce the gender hierarchies in their talk and coaching practice. Coaches contribute to the femininization of dual career pathways in Finland.